Erratum: Filip, S.; et al. Therapeutic Apheresis, Circulating PLD, and Mucocutaneous Toxicity: Our Clinical Experience through Four Years. Pharmaceutics 2020, 12, 940 - Stanislav Filip; Ondřej Kubeček; Jiří Špaček; Miriam Lánská; Milan Bláha (MDPI AG, 2020)
The following correction has been made to this paper [...]